Pengaruh Keamanan dan Risiko Kinerja Terhadap Keputusan Pembelian Online di Marketplace Tokopedia - Hakim, Syahrul Nur; Rachmawati, Eva (Jurnal Ekonomi Manajemen Perbankan, 2024)
This study aims to determine how security and performance risk affect online purchasing decisions both partially, simultaneously. The type of research used is survey research. The sample in this study were 75 respondents, namely management students of class 2020 using Tokopedia at Sangga Buana YPKP University Bandung. Data collection was carried out through an online questionnaire distributed using google form. Data analysis using descriptive analysis and multiple regression analysis. The results showed that the security variable did not have a significant effect on online purchasing decisions while the performance risk variable had a significant effect on online purchasing satisfaction and the two variables had a simultaneous effect on online purchasing decisions.